Iron Gall Ink Revisited: In Situ Oxidation of Fe(II)–Tannin Complex for Fluidic‐Interface Engineering - Lee, Hojae; Kim, Won Il; Youn, Wongu; Park, Taegyun; Lee, Sangmin; Kim, Taek‐Soo; Mano, João F.; Choi, Insung S. (Advanced materials (Weinheim), 2018)
The ancient wisdom found in iron gall ink guides this work to a simple but advanced solution to the molecular engineering of fluidic interfaces. The Fe(II)–tannin coordination complex, a precursor of the iron gall ink, transforms into interface‐active Fe(III)–tannin species, by oxygen molecules, which form a self‐assembled layer at the fluidic interface spontaneously but still controllably. Kinetic studies show that the oxidation rate is directed by the counteranion of Fe(II) precursor salts, and FeCl2 is found to be more effective than FeSO4—an ingredient of iron gall ink—in the interfacial‐film fabrication. The optimized protocol leads to the formation of micrometer‐thick, free‐standing films at the air–water interface by continuously generating Fe(III)–tannic acid complexes in situ. The durable films formed are transferable, self‐healable, pliable, and postfunctionalizable, and are hardened further by transfer to the basic buffer. This O2‐instructed film formation can be applied to other fluidic interfaces that have high O2 level, demonstrated by emulsion stabilization and concurrent capsule formation at the oil–water interface with no aid of surfactants. The system, inspired by the iron gall ink, provides new vistas on interface engineering and related materials science. The in situ oxidation of Fe(II) to Fe(III) in the Fe(II)–tannin complex, inspired by iron gall ink, provides a simple but advanced solution to the molecular engineering of fluidic interfaces. The versatility of this O2‐instructed synthetic strategy is demonstrated by the formation of micrometer‐thick, free‐standing films at the air–water interface and hollow capsules at the oil–water interface.